Computed Tomography and Magnetic Resonance Assessment of Choroid Plexus Xanthogranulomas - Sedat Altay (Forbes Tıp Dergisi, 2020)
INTRODUCTION: Seventy-five adult patients with retrospectively detected incidental choroid plexus xanthogranulomas (CPX) were evaluated with non-contrast brain computed tomography (CT) and contrast-enhanced brain magnetic resonance imaging (MRI) images. In this study, we aim to determine the imaging properties of CPX with CT and MRI, to evaluate the difference between white matter and CPX with diffusion-weighted imaging (DWI) and apparent diffusion coefficient (ADC), and ensure its potential use in the follow-up and treatment of CPX patients. METHODS: In this study, lesions between 5-25 mm were evaluated. CPX and white matter ADC measurements were performed on CT and MRI images in all lesions. An independent sample t-test was used for statistics. Cases with a history of cranial operation and any malignancy were excluded due to the possibility of metastasis. RESULTS: Bilateral CPX was detected in 41 and unilateral CPX in 34 patients. On CT, bilateral CPX calcifications were observed in 21 and unilateral calcifications in 44 patients. Calcification was not observed in brain CT in 10 patients. ADC (apparent diffusion coefficients) measurement was made from the widest and non-calcific parts of all lesions. ADC measurements were between 1.33-1.69x10-3/mm2/s and the mean value was 1.48x10-3/mm2/s. In all cases, the ADC value was lower relative to the white matter. ADC value was found to be higher and closer to the white matter ADC values than cases with a homogenous appearance in CPX patients with heterogeneous internal structure. DISCUSSION AND CONCLUSION: ADC value is useful in the diagnosis of CPX. In conclusion, the follow-up of the ADC value is useful in the diagnosis and follow-up of CPX.